Fungsi Zuhud Terhadap Kesehatan Mental (Studi Analisis Masa Pandemi Pada Ajaran Tarekat Idrisiyyah) - Husnul Qodim (Journal of Society and Development, 2021)
Some of the uncertainties that arise during the pandemic such as changes in learning adaptation, layoffs, and financial problems due to the negative economic impact that causes mental health problems for the community, but these impacts will not necessarily have an impact on tarekat worshipers, because tarekat is a path that a Sufi must take. (doers of Sufism) with the aim of being as close as possible to God, no longer looking for the world. This study tries to reveal how the Idrisiyah congregation is to maintain the mental health of the congregation through zuhud. With descriptive quantitative methods, it was found that there are two concepts of zuhud in business that can maintain mental health, namely the behavior of Sufism consumers and Sufism producers.